Analysis of cerebrospinal fluid adenosine deaminase level in tuberculous meningitis and validation of sensitivity and specificity - A. P., Shibeesh; Beevi B., Kadeeja; Valliyot, Balakrishnan; S. M., Sarin; Kumar K. K., Sarosh (International Journal of Research in Medical Sciences, 2018)
Background: Tuberculous meningitis is an important cause of morbidity and mortality in developing countries especially in India. The mortality associated with tuberculous meningitis is very high if not detected early and meticulous treatment is not given. CSF analysis and imaging are the most commonly used tools for diagnosis of meningitis. But these are often inadequate in making a definitive diagnosis. CSF Adenosine Deaminase estimation (ADA) is useful in differentiation of tuberculous meningitis from non-tuberculous meningitis. Though few studies have proved efficacy of Adenosine Deaminase level for the diagnosis, studies to assess the sensitivity and specificity of ADA levels were limited. This study was conducted to assess its usefulness and to validate the sensitivity and specificity of ADA level in tuberculous meningitis (TBM). Methods: This was a prospective study conducted at Academy of Medical Sciences, Pariyaram for a period of 18 months from December 2013 to June 2015, Adenosine deaminase level was studied in the cerebrospinal fluid of 50 patients who got admitted with symptoms and signs of meningitis in the medical wards and intensive care units who fulfilled the inclusion criteria. Results: In this study 50 patients were diagnosed clinically and with CSF analysis as meningitis. The mean cerebrospinal fluid adenosine deaminase activity was 23.08+17.5in Tuberculous meningitis 3.8 +1.92U/l in Bacterial meningitis and 4.8+2.3U/l in Viral meningitis. The adenosine deaminase activity in Tuberculous meningitis cases were significantly higher than non-tuberculous meningitis. The sensitivity and specificity of this test for diagnosis of tuberculous meningitis was 90% and 100% respectively with ADA value of more than 10U/L. Conclusions: This study found out that estimation of CSF Adenosine level is a very useful test for the diagnosis of tuberculous meningitis. The sensitivity and specificity attained in this study were comparable to other studies. This study also found out that ADA estimation is very useful in distinguishing tuberculous and viral meningitis.